Hubungan Beban Kerja Dan Lingkungan Kerja Dengan Kejadian Kecelakaan Kerja Pada Perawat Ruang Rawat Inap Di Rsud Banyumas - Dewi Sofiantika; Rakhmat Susilo (Jurnal Keperawatan Muhammadiyah, 2020)
Background: In 2017 The number of work accidents which was reported reached 123,041 cases, in 2018 it reached 173,105 cases. Each year, the Workers Social Security Agency served 130 thousand work accident cases, from minor cases to fatal cases (Jamkesindonesia, 2019). This study aimed to determine the relationship between work load and work environment towards work accident occurance in inpatient nurses of RSUD Banyumas.Method: Quantitative descriptive research using cross sectional design was used in this study. The population of 11 inpatient rooms consisted of 122 inpatient nurses in RSUD Banyumas. The simple random sampling was used as the technique to collect the sample. There were 55 respondents in the inpatient rooms of RSUD Banyumas. Questionnaire and observation sheet were used as the research instrument. The data were analyzed by using chi square test.Results:  There were 44 respondents (80%) with the high level of workload. There were 47.76% of all respondents who were doing direct nursing activities. There were 33 respondents (60%) who had good nurses work environment. There were 29 respondents (52.72%) who got nurse work accident.Conclusion: There is a relationship between workload and work accident. The result obtained p value of 0.024 which was smaller than α = 0.05. There is a relationship between work environment and work accident. The result obtained p value of 0.32 which was smaller than α = 0.05. There is a significant relationship between workload and work accident and there is a significant relationship between work environment and work accident in inpatient nurses of RSUD Banyumas.Keywords: work accident, work environment, workload, nurses, hospital